Primary B-cell lymphoma of the uterine corpus – case report and review of the literature - Moszyńska-Zielińska, Małgorzata; Sobotkowski, Janusz; Gottwald, Leszek; Kordek, Radzisław; Błasińska-Morawiec, Maria; Ciałkowska-Rysz, Aleksandra (Menopause Review/Przegląd Menopauzalny, 2008)
Primary B-cell lymphoma is a lymphoblastic B-cell malignant tumour with very aggressive course. Its abdominal form involving internal genital organs is rare. We report the case of a 67-year-old woman treated due to abdominal B-cell lymphoma. The patient presented postmenopausal uterine bleeding. During laparotomy total abdominal hysterectomy with bilateral salpingo-oophorectomy was performed. Pathologic examination revealed a primary uterine: diffuse large B-cell lymphoma (DLBCL), CD20 (+). After surgery, immunochemotherapy (R-CHOP) was conducted. The patient, 12 months after surgical treatment, is still under control in our Oncological Centre. No signs of recurrence have been detected so far.